PARTISIPASI POLITIK PEREMPUAN: STUDI PEREMPUAN DALAM PEMILIHAN KEPALA DAERAH JAWA TENGAH TAHUN 2008 - Suhardiyanto, Andi; Lestari, Puji (Forum Ilmu Sosial, 2008)
The participation from the female constituent at the election for central Java Governor 2008 waslow. It mostly caused by their understanding of the elections mechanism itself. The hottest issues aboutthe candidates that rouses then recommending people to join and vote. Another factor that impulse thefemale constituent to vote were, vision and mission of the parties, the candidate’s performance, family’sconsideration, and parties performance who support any candidate. Our patriarchate culture bound tothe politic discourse, it had raise the misperception that power was identical to misogynic, the term thatalways refers to male. It took female on to domestic sector, where they should be obey any commandno matter what.Keywords : Female constituent, election Central Java Governor